Keanekaragaman dan Kelimpahan Makrozoobentos di Pantai Batu Belubang Bangka Tengah - Dela Angelia; Wahyu Adi; Sudirman Adibrata (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2019)
ABSTRACT Batu Belubang Beach is located in the area of ​​Batu Belubang Village, Pangkalan Baru District, Central Bangka Regency. This area has good marine resource potential, but over time with the increasingly sophisticated technology the potential for marine resources is not only used by fishermen to find fish but also used by the community for floating mining activities. This can affect the existence of marine ecosystems, especially macrozoobenthos, which are organisms that are very vulnerable to environmental changes. This study aims to analyze the diversity index, uniformity and dominance of macrozoobenthos in the coastal region of the middle bangka belubang rock. Date retrieval was carried out in March 2018 on Batu Belubang beach, the research method used was purposive sampling with the taking of 3 stations of each station divided into 3 substations 3 times. Data analysis using the correlation analysis method, the parameters taken are the physical chemical parameters of the water. The results of data analysis obtained in the diversity index value is 1.06 with the medium category. The uniformity index value obtained is equal to 0.22 with a low category and the dominance index obtained is 0.3 with a low category. The results of the correlation analysis obtained from the physical chemical parameters on the correlation results of TSS, depth and mud with very influential categories with a correlation value> 0.75-0.99. The results of the correlation on the value of temperature, pH, current velocity and DO are categorized as strong correlations with a value of> 0.5-0.75 and the correlation value of sand is categorized sufficiently with a value of> 0.25-0.5.